2022
DOI: 10.4251/wjgo.v14.i10.2014
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of a serum tumor biomarkers scoring system for clinical stage II/III rectal cancer with neoadjuvant chemoradiotherapy

Abstract: BACKGROUND Multiple classes of molecular biomarkers have been studied as potential predictors for rectal cancer (RC) response. Carcinoembryonic antigen (CEA) is the most widely used blood-based marker of RC and has proven to be an effective predictive marker. Cancer antigen 19-9 (CA19-9) is another tumor biomarker used for RC diagnosis and postoperative monitoring, as well as monitoring of the therapeutic effect. Using a panel of tumor markers for RC outcome prediction is a practical approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A study shows that pre-treatment serum CEA levels are the most important clinical predictor of tumor response after TNT. 8 A study has found that the higher the CEA level before treatment, the lower the responsiveness of TNT. 9 Some studies have found that pre-treatment CEA levels greater than 2.5 µg/L are associated with lower oCR rates (p = 0.015) and lower tumor progression rates (p = 0.006).…”
Section: To the Editorsmentioning
confidence: 99%
“…A study shows that pre-treatment serum CEA levels are the most important clinical predictor of tumor response after TNT. 8 A study has found that the higher the CEA level before treatment, the lower the responsiveness of TNT. 9 Some studies have found that pre-treatment CEA levels greater than 2.5 µg/L are associated with lower oCR rates (p = 0.015) and lower tumor progression rates (p = 0.006).…”
Section: To the Editorsmentioning
confidence: 99%